The Dynamics of Puberty and Motivation to Learn the Qur'an: A Case Study of Adolescents at TPQ Ar Rosyid, Central Java - Nur Setiani; Shafa Alistiana Irbathy; Naomi Fahma; Rina Endang Purwanti; Shafira Apriliana Roselani; Uly Kusumo Wati (Bulletin of Pedagogical Research, 2024)
This study investigates the factors influencing adolescents’ motivation to learn the Qur'an during puberty within the educational settings of madrasahs and Islamic boarding schools (pesantrens). Puberty represents a crucial stage of human development characterized by profound physical, emotional, and social transitions, which can significantly impact students' engagement in religious education—particularly in the consistent and disciplined practice of Qur’anic learning. Employing a quantitative research design, data were collected through structured questionnaires distributed to 150 students aged 12–15 across various institutions. Descriptive statistics and regression analysis were used to examine the relationships among key variables, including family support, instructional methods, and psychological conditions, and their influence on students’ motivation. The results reveal that strong family support and interactive, student-centered teaching strategies are positively correlated with higher levels of learning motivation. Furthermore, emotional self-regulation and a clear understanding of the value of Qur’anic memorization play a vital role in sustaining motivation during this transitional phase. The study also highlights common challenges faced by adolescents, such as decreased concentration and mood fluctuations, underscoring the need for adaptive pedagogical approaches and increased collaboration between educators and parents. These findings offer practical insights for religious education practitioners in developing more effective, engaging, and supportive Qur'anic learning programs tailored to the developmental needs of adolescents undergoing puberty.